An Analytical Study of the State's Role within the Framework of Islamic Economics: Sayyid Qutb's Perspective - JAKA SUSILA, HARYADI; Susila, Haryadi Jaka (Sekolah Tinggi Ilmu Ekonomi Balikpapan, 2025)
This study aims to examine Sayyid Qutb's views on the role of the state within the framework of the Islamic economic system. Using a qualitative approach and literature review method, this research delves into the fundamental concepts of Islamic economics proposed by Qutb and their application in the economic policies of Muslim-majority countries. The study reveals that, according to Qutb, the state plays a role beyond merely being a regulator; it is an entity responsible for ensuring the fair and equitable distribution of wealth. Qutb emphasizes that the primary goal of Islamic economics is to achieve social justice, reduce economic disparities, and avoid the dominance of capitalism that can lead to inequality. Furthermore, Qutb highlights the importance of the state's role in managing social instruments, such as zakat and waqf, which serve as tools for wealth redistribution and economic empowerment of society. This research is expected to contribute to a deeper understanding of the implementation of Islamic economic principles in state policies and their impact on achieving a fairer economic welfare.